Data set of multi-objective optimization of diesel engine parameters - R. Sathish Kumar; K. Sureshkumar (Data in Brief, 2019)
This data article presents the experimental data set on the optimization of four important parameters which are type of blending fuel, blending ratio, compression ratio and injection timing for four objective functions namely higher brake thermal efficiency, lower brake specific fuel consumption, lower oxides of nitrogen emission and lower unburnt hydrocarbon emission using grey relational analysis and orthogonal array based experimental design. Each parameter was fixed with three levels and L9 orthogonal array has been chosen for experimental analysis. The data obtained from the experimental work reported that butanol as blending fuel, 40% of maximum blending ratio, compression ratio of 16:1 and injection timing of 26 °CA before top dead centre were identified as optimized set of parameters. Keywords: Multi-objective optimization, Grey relational analysis, Orthogonal array, Design of experiments, Analysis of variance, Diesel engine